Govor v sodobnem slovenskem romanu - Zupan Sosič, Alojzija (Slavistična revija, 2015)
Research in the contemporary Slovene novel (1990-2015) has shown an increase in the share of speech. The main reason for this is a tendency for mimesis in speech as a means of characterization. This tendency was analyzed in the novel Čefurji raus! by Goran Vojnović. There is also a tendency for deautomatization and renovation of narration, which was analyzed in the novel Da me je strah? by Maruša Krese. The former is an example of a traditional presentation of monologue and dialogue, i.e., with speech tags and dialogue as a part of a screenplay, whereas the latter is a combination of monologue, dialogue, internal monologue, and free indirect speech, all of which make Krese's novel much more contemporary/innovative and complex. It is this multi-perspective syncretism of various speech techniques that invites innovative social criticism.
Keywords: "Čefurji raus"; "Da me je strah?"; contemporary Slovene novel; dialog; dialogue; free indirect speech; govor; internal monologue; Krese, Maruša, 1947-2013; mediation of speech; monolog; monologue; notranji monolog; Slovene literature; slovenska književnost; sodobni slovenski roman; stream of consciousness; tok zavesti; Vojnovič, Goran, 1980-